Caspian Sandy Natural Focus: Phylogenetic History and Origin of Yersinia pestis Strains - P. A. Goryunova; G. A. Eroshenko; L. M. Kukleva; E. A. Naryshkina; E. A. Sosedova; N. S. Chervyakova; V. V. Kutyrev (Проблемы особо опасных инфекций, 2022)
The purpose of the work was to analyze the phylogenetic relations and origin of Yersinia pestis strains isolated in different periods of epizootic activity of the Caspian sandy natural focus (CSNF) of plague in the XX–XXI centuries.Materials and methods. We used 40 Y. pestis strains from CSNF and adjacent plague foci, isolated in 1922–2015. Carried out was whole genome sequencing of 19 Y. pestis strains from CSNF. Phylogenetic analysis was performed using whole genome SNP analysis based on 1914 identified SNPs. The search for marker SNPs was conducted using the Snippy 4.6 software. The phylogenetic tree was constructed using the Maximum Likelihood algorithm, the GTR nucleotide substitution model.Results and discussion. The whole genome SNP analysis has revealed that Y. pestis strains of the medieval biovar from CSNF belong to 2.MED1 phylogenetic lineage and fall into two major branches. One of them circulated in the focus in the first half of the XX century, and the other – in the second half of the XX – early XXI centuries. It is shown that strains of the first branch were the cause of outbreaks and individual cases of plague in the CSNF in the first half of the XX century. They are closely related to strains from the Caspian North-Western steppe and Volga-Ural sandy natural plague foci, which caused numerous outbreaks with high mortality rate in the same period. Y. pestis strains from the CSNF of the second half of the XX and early XXI centuries belong to the second phylogenetic branch of the 2.MED1 line, at the node of which the strains from the Northern Aral Sea region of 1945 lay. The latter were the predecessors of all strains isolated in the CSNF after a long inter-epizootic period that occurred in the middle of the XX century. There can also be traced a genetic relation between the strains from CSNF and the Dagestan plain-foothill focus.